Scale-Up of Magnetocaloric NiCoMnIn Heuslers by Powder Metallurgy for Room Temperature Magnetic Refrigeration - Puglielli, Francesco; Mussi, Valerio; Cugini, Francesco; Sarzi Amadè, Nicola; Solzi, Massimo; Bennati, Cecilia; Fabbrici, Simone; Albertini, Franca (Frontiers in Energy Research, 2020)
We present a new approach for a large-scale production of the rare-earth free NiCoMnIn Heusler alloy for room temperature magnetic refrigeration applications. This class of compounds has recently attracted attention, thanks to the large reversible isothermal entropy change (ΔSiso) and adiabatic temperature change (ΔTad) associated to a first-order magnetostructural phase transition. A large-scale production method, however, has not yet been proposed. For giant magnetocaloric materials and especially for Heusler compounds, the synthesis has a predominant role in tailoring the physical–chemical properties, due to the high sensitivity of the first-order transition characteristics on chemical composition and microstructure. Up to 250 g of the nominal composition Ni45.7Co4.2Mn36.6In13.3 alloy was prepared in a unique sample starting from industrial-grade powdered elements. The phase transition temperatures and magnetocaloric properties were investigated by magnetic and direct adiabatic temperature measurements and were found to be homogeneous in the whole sample. The mechanical stability of the produced alloy and its workability were investigated. A low-temperature thermal treatment was identified and showed promising results by reducing hysteresis and transition width.